The Effect Of Production Costs And Operational Costs On Net Profit Of Jamu Dapoer Niswah Medan Marelan District - Putri, Sri Eka; Anggraini, Tuti; Nurwani (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect of production costs and operating costs on net income partially and simultaneously. This type of research is quantitative research with an associative approach. The location of this research is UMKM Jamu Dapoer Niswah, Medan Marelan District. The data used is secondary data. Secondary data in this study is in the form of profit and loss statements for 2020 – 2022. The population and research sample totaled 36 months, starting from January 2020 to December 2022 using a saturated sampling technique. The analytical method used is descriptive statistical analysis, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, partial significant test (t statistical test), simultaneous significant test (F statistical test) and R2 test (coefficient of determination). by using SPSS 25 software. The results showed that (1) The test results showed that the production cost variable obtained a t-count value of 3.021 ≥ t-table of 1.68830 and a significance value of 0.005 ≤ 0.05. Therefore it can be concluded that the production cost hypothesis has a positive and significant effect on net income. (2) The test results show that the operational cost variable has a t-count value of 8.477 ≥ t-table 1.68830 and a significance value of 0.000 ≤ 0.05. Therefore, it can be concluded that the production cost hypothesis has a positive and significant effect on net income. (3) The test results show that the variable production costs and operational costs obtain an F-count value of 3095.702 ≥ F-table 3.28 and a significant value of 0.000 ≤ 0.05, it can be concluded that the variable production costs and operating costs simultaneously significant effect on net income.